Synergy of Pd atoms and oxygen vacancies on In2O3 for methane conversion under visible light - Lei Luo; Lei Fu; Huifen Liu; Youxun Xu; Jialiang Xing; Chun-Ran Chang; Dong-Yuan Yang; Junwang Tang (Nature Communications, 2022)
CH4 oxidation to high value chemicals under mild conditions through photocatalysis confronts critical issues regarding both conversion and selectivity. Here, atomic Pd and oxygen vacancies were integrated on In2O3 nanorods, leading to visible-driven CH4 conversion with a remarkable yield of oxygenates and high selectivity of primary products.